PENGARUH MODUL FISIKA DASAR BERBASIS FLIPBOOK TERINTEGRASI PHET DALAM BIMBINGAN AKADEMIK TERHADAP MOTIVASI MAHASISWA - HASANAH, NAIMAH (Universitas Islam Ahmad Dahlan, 2026)
Learning motivation is a critical determinant of student’s academic success, particularly in basic physics courses. This study aims to examine the effect of a flipbook-based practicum module integrated with PhET simulations, implemented within an academic guidance framework, on students' learning motivation at STAIN Mandailing Natal. The study employed a quantitative approach with a One-Group Pretest-Posttest design. The sample consisted of 32 students from the Science Education Study Program, selected through total sampling. Data were collected using a learning motivation questionnaire based on ARCS dimensions (Attention, Relevance, Confidence, Satisfaction), which was validated (Aiken's V = 0.84–0.92; α = 0.89). Data were analyzed using Paired Sample t-test, Cohen's d, and Normalized Gain. Results indicated: (1) a significant increase in learning motivation after the intervention, t(31) = 16.32; p < 0.001; (2) a very large effect size (Cohen's d = 2.88) with a moderate improvement category (N-Gain = 0.46); (3) the Confidence and Satisfaction dimensions showed the highest gains. It is concluded that integrating flipbook-PhET modules within academic guidance effectively enhances students' learning motivation. This study provides empirical contributions to the development of innovative academic guidance models in Islamic higher education institutions.